Effect Of Binder On Bioceramic Surface Roughness When Millin - RAMLI, MUHAMMAD HAZIM; Bin Rafai, , Noor Hakim (Research Progress in Mechanical and Manufacturing Engineering, 2024)
There are too many road incidents that result in permanent disability, such as bone fractures requiring bone replacement. Hydroxyapatite (HAP) is a chemical compound with analogous properties to the mineral component of human bones and hard tissues. Therefore, it is commonly used as a bone implant material and, more commonly, as a bioactive coating. Along with the various biomedical applications, numerous HAP synthesis techniques for producing HAP powder have been developed. In this study examines the effects of binders on bioceramic surface roughness when milling. The sample is prepared for machining with varying binder percentages. Using the dry mixing and compaction technique, samples are prepared. The ratio between PEG and PVA samples ranges from 1% to 4% by weight. The samples are sintered in the furnace using a heating rate of 2°C/min and a two-hour soaking period. The temperature is set to a constant 1200°C degrees Celsius. All of the samples were machined using a Cnc milling machine with a constant spindle speed of 318.471 rpm, constant cutting speed of 27 m/s, constant feed rate of 0.046 mm, and constant depth of cut of 0.1 mm. Using SEM, surface roughness, modulus of rupture Vickers hardness, XRD, density, and porosity, all samples are analysed. The quantity of binders that influence the machining of bioceramics was ascertained through sample preparation and testing. The samples with the maximum hardness contain the most PEG, while those with the lowest hardness contain the most PVA. Results were obtained, and the optimal suitable sample composition was (PEG 4 PVA 1). The conclusion is then that the produced HAP samples are compatible with machining and that the binders do influence machining, hardness, and surface roughness. Beside the composition of the binder influences the density and porosity of the produced HAP samples.